Immigrants’ sense of belonging to Canada by province of residence - Max Stick; Christoph Schimmele; Maciej Karpinski; Seyba Cissokho (Economic and Social Reports)
Sense of belonging to Canada is a well-documented measure of immigrants’ social integration. However, it differs by sociodemographic characteristics such as years since immigration, age at immigration, admission category and population group. This study uses the 2020 General Social Survey to examine whether immigrants’ sense of belonging to Canada depends on their province of residence.